Gambaran Kepemimpinan Pembina Kegiatan Ekstrakurikuler Pramuka di SMA Adabiah Padang - Hanifah Hanum; Solfema Solfema; Jalius Jalius (Universitas Negeri Padang, 2018)
This research is motivated by, the scout member in SMA Adabiah Padang has good discipline, allegedly caused by the leadership of scout leader. The purpose of this study is to describe the leadership of scout leader which includes: the leadership of the coach in moving the scout leader's leadership in guiding the scout members, and the leadership of the builder in influencing the scout members. This type of research is descriptive quantitative. The population in the study amounted to 230 people. Sampling technique in this research is random sampling technique. The number of samples in this study is 46 members of Boy Scouts on extracurricular scout activities. Data collection techniques used are questionnaires, while the data collection tool uses a list of statements. Data analysis techniques using the formula percentage. The results showed that the leadership of scout extracurricular activities is very good, it can be seen from: (1) the leadership of the supervisor in the move, (2) the leadership of the supervisor in directing, (3) the leadership of the supervisor in influencing. It is suggested to the principal to increase the leadership of scout leader, to the coach in order to maintain the leadership system, to the scout members in order to apply it in everyday life.